Pemetaan Partisipatif melalui Aplikasi GPS untuk Mitigasi Kon ik Batas Wilayah: Studi Kasus di Desa Adat Nyuh Kuning, Ubud, Bali - Sardiana, I Ketut; P. Windia, I Wayan (Jurnal Kajian Bali (Journal of Bali Studies); Vol 8 No 1 (2018): MODAL BUDAYA PARIWISATA BALI, 2018)
Customary village con ict triggered by border disputes become an important issue occurred in Bali in recent decades. Unclear village boundaries can disrupt the tranquility of the traditional village concerned. This paper is intended to examine the participatory mapping approach through application of Global Possitioning System (GPS) for mapping the area of customary villages. The present research was conducted in Desa Adat Nyuh Kuning, Ubud, Gianyar, Bali. The study revealed that participatory mapping through the application of GPS is suitable for the mapping of customary villages. This approach produces a map of the village with high accuracy that the depiction of the boundary line in accordance with the coordinates in the eld. Delimitation of the territory by involving and ge ing agreement from neighboring villages will be able to prevent border disputes with neighboring indigenous villages.